Inter system handoff management in cellular mobile networks / Syamil Khalid - Khalid, Syamil
This paper presents a handoff technique which supports mobility between dissimilar networks. The boundary cell of cellular network system is designed by using MATLAB design software. A simulation model is developed to study the performance of the relative signal strength with hysteresis and threshold (RSS-HT) algorithm. The theoretical analysis and simulation result are studied to evaluate the handoffs parameters.